Aristotle and Greed - Velázquez Jordana, José Luis (ΠΗΓΗ/FONS, 2020)
Aristotle’s notion of particular justice has been the object of a long controversy focused on the difference between particular injustice and other vices, and the difficulty of distinguishing the emotional content of just actions from the unjust actions of the covetous. This paper reconstructs Aristotle’s arguments and presents the most relevant objections to the representation of the vice of greed by J.O. Urmson and B. Williams. It concludes with some observations to mitigate these objections.